Gim edukasi berbasis android sebagai optimasi pembelajaran daring di masa pandemi Covid 19 - Fitria Nur Hasanah; Cindy Taurusta; Rahmania Sri Untari; Dini Nurul Hidayah; Rindiani Rindiani (JINoP (Jurnal Inovasi Pembelajaran), 2021)
The innovation in Information and Communication Technology (ICT)-based learning media is a critical learning alternative during the Covid-19 pandemic. One of the ICT-based learning media is android-based educational games. This research aims to develop android-based educational games on object-oriented programming (OOP) courses for Information Technology Education (ITE) students and to find out the feasibility of this product in online learning optimization. This research employed Research and Development (R&D) with Analysis, Design, Develop, Implement, Evaluate (ADDIE) development model. Participants of this research were the fifth-semester ITE students. Questionnaires validated by learning material and media experts were tested on limited groups before being distributed to the participants. Results show that the feasibility level on the material content aspect is 93.2%, and the language aspect is 93.3%, referring to very feasible criteria. The feasibility level on the content quality is 90%, the design and audio aspects are 95%, and interaction and feedback are 93.75%, referring to very feasible criteria. The trial results of the limited group are 96% with very feasible criteria. These findings indicate that android-based educational games are feasible and can be implemented in the learning process.